IFNG +874A/T Polymorphism Among Asymptomatic HTLV-1-Infected Individuals Is Potentially Related to a Worse Prognosis - Queiroz, Maria A. F.; Azevedo, Vânia N.; Amoras, Ednelza da S. G.; Moura, Tuane C. F.; Guimarães Ishak, Marluísa de O.; Ishak, Ricardo; Vallinoto, Antonio C. R.; Martins Feitosa, Rosimar N. (Frontiers in Microbiology, 2018)
HTLV-1 infections are persistent and frequently latent; however, productive infections trigger different types of immunological responses that utilize cytokines to control infection. The present study investigated the role of IFNG +874A/T polymorphisms among 153 HTLV-1-infected individuals (33 clinically diagnosed with TSP/HAM, 22 with rheumatologic manifestations, 2 with dermatitis, 1 with uveitis, and 95 asymptomatic patients) and 300 healthy control individuals. Genotyping and proviral HTLV-1 load assessment were performed using real-time PCR assays, and the plasma levels of IFN-γ were measured using an enzyme immunoassay (ELISA). Genotype frequencies were not significantly different, but the presence of the T allele was higher (p < 0.0142) among the asymptomatic patients. Plasma levels of IFN-γ were significantly higher (p < 0.0137) among those with the TT genotype. Their proviral load was also higher, although this elevation did not reach statistical significance. There was no difference in the IFN-γ plasma levels among the symptomatic patients, even when ranked according to disease severity (TSP/HAM or rheumatologic manifestations). However, the difference among asymptomatic patients with the T allele was significantly higher (p < 0.0016) and similar to the plasma levels observed among symptomatic individuals. These results suggest that the IFNG +874A/T polymorphism may modulate the plasma levels of IFN-γ during HTLV-1 infection. Asymptomatic carriers of the polymorphic genotypes appear to develop an inflammatory response in a shorter timeframe, triggering progression to HTLV-1-related symptoms and disorders. These results further suggest that HTLV-1-infected asymptomatic individuals expressing the IFNG +874A/T polymorphism should be monitored more closely in order to readily detect the increase in clinical symptoms, as these patients are potentially at risk of a poor prognosis and should therefore start available treatment procedures earlier.